Pengaruh Koneksi Militer Terhadap Kinerja Keuangan Perusahaan pada Perusahaan Sub Sektor Logam dan Mineral Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2023 - Agam Akmaluddin; Elviza Elviza; Intan Rizkia Chudri (AKUNTANSI 45, 2025)
The purpose of this study is to evaluate the impact of the presence of military connections on financial performance in companies belonging to the metals and minerals sub-sector, and listed on the IDX during the period 2017 to 2023. The main focus of the problem in this study is whether the presence of military connections has an influence on the company’s financial performance. The approach used in this study is panel data regression, with data processing done using EViews13 software. The sample selection was carried out using purposive sampling technique, which resulted in 6 companies as research samples, with an observation time span of 7 years. Overall, there are 30 observation units. This study analyzes two main variables, namely military connections and company financial performance, both of which are measured using a ratio scale and sourced from secondary data. Based on the results of the analysis, it was found that military connections have an influence on the financial performance of companies included in the metals and minerals sub-sector on the IDX.